Semiotika Iklan 3 Always On “Bebas Kini Semakin Nyata” - Irma Tri Anggraeni, Irma (ISI Press Institut Seni Indonesia Surakarta, 2022)
This paper discusses about how the 3 Always On try to advertise and tried to give a berakthriugh to the concept of freedom in people’s life. This concept oftenly being mistranslated. Although it is said to be free, the traditional form of stigma is actually able to break the concept of freedom itself. In the end, the term of a free and equal woman has never materialized. The 3 Always On adverstisement provides mild sarcastic of criticism to promote its produts, arguing on that it is unlimited. This explanation was being explained with the theory concept of Semiotic Theory by Roland Brathes.